Comparative study of Alvarado score and RIPASA score in the diagnosis of acute appendicitis - Jaiswal, Anand K.; Mathur, Sujeet K.; Kumar, Santosh; Tripathi, Durgesh K.; Kumari, Sudha (International Surgery Journal, 2023)
Background: Acute appendicitis is one of the most common surgical emergencies. Immediate and accurate diagnosis, mainly based on clinical assessment and laboratory results, is of paramount importance in order to reduce complications and mortality rates. Challenging diagnosis and fears of missing an inflamed appendix may lead to a negative appendectomy. Many scoring systems have been developed to reduce ambiguities in the diagnosis of appendicitis. The aim of the present study was to compare the efficacy of Alvarado score and RIPASA score in the diagnosis of acute appendicitis. Methods: This study was conducted in the Department of Surgery, Nehru Hospital, BRD Medical College, over a period of 12 months. A total number of 50 cases with a clinical diagnosis of acute appendicitis were studied. Informed consent was obtained from all registered cases. Results: 48% were male and 52% were females in the study. 70% belonged to <40 years and 30% belonged to >40 years. Among 50 patients, in patients ≥40 years of age, appendicitis was diagnosed in 10 patients and in patients <40 years of age, 24 were diagnosed with appendicitis. Among 50 patients, 24 were males out of which 19 were diagnosed with appendicitis compared to 15 out of 26 females. Anorexia and tenderness in RLQ were present in 100% patients. 100% patients had anorexia, RIF pain and tenderness. Alvarado and RIPASA score showed sensitivity 64.7% and 88.2% respectively. Conclusions: The difference in the diagnostic accuracy between Alvarado and RIPASA scoring system is significant indicating that the RIPASA score is a much better diagnostic tool for the diagnosis of acute appendicitis. When the ROC curve was observed the area under the curve is high for RIPASA scoring system.